Simulasi Model Matematik Dampak Penerapan Kebijakan Mandatori Blending Biodiesel-Solar terhadap Kebutuhan Lahan Perkebunan Kelapa Sawit dan Tingkat Emisi CO2 - Petir Papilo; Hartrisari H (JIEMS (Journal of Industrial Engineering and Management Systems), 2017)
The implementation of the mandatory policy of mixing (blending) between biofuels into the fuel has an impact on the icreasing of biodiesel needs, increasing the oil palm plantation area and environmental impact in the form of CO2 emissions by the year 2025. This study aimed to identify the level of each factor needs as well as the impact on the environment. Through the analysis of the design of mathematical models, it is known that the gradually until 2030 has been an increased need for biofuels amounted 14.79 million KL. In an effort to meet the needs of the necessary biofuel oil palm plantations of 35,2 million hectares and an increase in CO2 emissions of 5,41 Gg t CO2.Keywords: Biodiesel, CO2 Emission, Land Area, Mandatory Policy. Biodiesel, CO2 Emission, Land Area, Mandatory Policy